Mulheres, trabalho e economia solidária: estudo de caso da associação de agricultoras de um município do Campo das Vertentes de Minas Gerais - Souza, Cristiane Reis de (2022)
Historically, women have occupied lower positions in relation to men in the world of work and the gender and work approach in Solidary Economy may contribute to the construction of an economy paradigm where the possibility of overcoming those differences is presented. The strengthening of the participation of women in these practices has been taking place through projects led by them, based on ideals of mutual help and self-sustainability, with the purpose of generating income, creating spaces for experience exchange, restoring self-esteem and promoting the integration of people groups with a common interest. The present paper has the purpose of inserting the theoretical reflections on the Sexual Division of Labor in the context of the Solidary Economy practices, and it has the scope of examining, from women “place of speech”, and reflecting, through the spectacles of gender perspective, how they problematize the issues of labor, and in what way the Solidary Economy practices add to the problematization and the resignification of their work. The present Case Study used as resources qualitative tools of data collection and analyses, like narrative interviews, direct observation and documental analyses. In this research, the women are the holders of the word, and they tell us, from their daily life, their life and work experiences. The research was carried out with the women associated to AMAGRI – Associação das Mulheres Agricultoras de Perdões, (Women Farmers Association of the city of Perdões) an association that has the purpose of joining together rural women producers, craftswomen and stallholders, in order to strengthen their activities. The theoretical perspectives of the issues related to labor and gender, brought about by those studying the Sexual Division of Labor and Feminist Economy helped to observe, from the interviewee’s narratives, patterns that keep on repeating themselves, like the unequal Division of household and care work, and the work overload which prevent the women from engaging the activities of the Association in a more active way. The studies on Solidary Economy have helped to identify important achievements resulting from the collective participation in the Association, like the strengthening of women protagonism concerning labor, the fighting the invisibility of women’s work and the gain of autonomy and personal well-being. The Association showed itself as a potential sharing space, mutual help, and development of citizen consciousness.